2005
DOI: 10.1007/s11095-005-4581-4
|View full text |Cite
|
Sign up to set email alerts
|

Formulating Paclitaxel in Nanoparticles Alters Its Disposition

Abstract: These data indicate that formulation of paclitaxel affects its clearance and distribution into tissues, with preferential accumulation of nanoparticles in the liver, spleen, small intestine, and kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…Previous studies using the standard formulation of paclitaxel solubilized with polyethoxylated castor oil revealed a terminal t1/2 of 1.9 hours. 15 The prolonged t1/2 in CTI 52010 can be exploited for therapeutic gain in tumors of the liver and spleen, providing a potential therapeutic advantage over standard paclitaxel formulations. We chose a 28-day washout period between treatments based on the metabolism and clearance of other chemotherapeutic agents, and without prior knowledge of the extended half-life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using the standard formulation of paclitaxel solubilized with polyethoxylated castor oil revealed a terminal t1/2 of 1.9 hours. 15 The prolonged t1/2 in CTI 52010 can be exploited for therapeutic gain in tumors of the liver and spleen, providing a potential therapeutic advantage over standard paclitaxel formulations. We chose a 28-day washout period between treatments based on the metabolism and clearance of other chemotherapeutic agents, and without prior knowledge of the extended half-life.…”
Section: Discussionmentioning
confidence: 99%
“…However, many nanoparticulate formulations use a polymeric coating such as gelatin. 15 CTI 52010 is produced using precipitation with compressed antisolvents, and polymeric coatings are not needed. Due to the production methods used, CTI 52010 contains only paclitaxel in nanoparticulate form, and avoids the toxicities associated with gelatin or other matrices used in other nanoparticle production methods.…”
Section: Discussionmentioning
confidence: 99%
“…3) when paclitaxel was administered. Aggregate toxicity is not likely for the reversed sequence because paclitaxel has a much shorter elimination halflife compared with doxorubicin HCl liposome (1-2 versus 20 -35 h) (Gabizon et al, 2003;Yeh et al, 2005), and over 99% of the paclitaxel dose would have been eliminated in 48 h when doxorubicin HCl liposome was administered. These data indicate tumor priming did not enhance the toxicity of doxorubicin HCl liposome.…”
Section: Enhances Delivery and Efficacy Of Nanomedicines 83mentioning
confidence: 99%
“…This prolonged circulation time together with EPR effects allowed for much higher accumulation of the drug at tumor sites (10-fold higher than PTX and 6-fold higher than PEG-PTX after 2 h of injection and 6-and 4-fold higher, respectively, after 24 h of injection) [109]. In conclusion, the high delivery efficacy of PTX by SWCNT subsequently resulted in tumor inhibition of SWCNT-PTX (5 mg/kg PTX) for the 4T1 tumor model known to be resistant to PTX treatments [138][139][140][141][142][143]. It has been shown that nanotube drug delivery is promising for high treatment efficacy and minimum side effects for future cancer therapy with low drug doses.…”
Section: Covalent Methodsmentioning
confidence: 99%